Efficacy of Literature–Based Instructional Strategies on Pupils’ Awareness of and Attitude to Child Rights in Kwara State, Nigeria (2015)
Nigeria has domesticated the Convention on the Rights of the Child, but majority of Nigerian children are still being denied their rights to survival, development, participation and protection from inhuman treatment and exploitation. Lack of awareness of child rights among Nigerian children is one of the major factors identified with child rights abuse. Earlier attempts on awareness creation were limited to activities of media and advocacy groups without empirically finding out the effectiveness of strategies such as Drama-Based Instructional Strategy (DBIS), Poem/Song-Based Instructional Strategy (PSBIS) and Prose-Based Instructional Strategy (PBIS) that can be adopted to increase awareness and influence pupils‘ attitude to child rights. This study, therefore, determined the efficacy of these three modes of literature-based instructional strategies on pupils‘ awareness of and attitude to child rights in Kwara State, Nigeria. The moderator effects of school location and parents‘ educational background were also examined. Pretest-posttest control group, quasi-experimental design with a 4x2x2 factorial matrix was adopted. Kwara Central senatorial district was purposively selected because of the rampant incidence of child rights abuse observed in the district. One each of rural and urban primary school was randomly selected from each of the four Local Government Areas in the district. All the primary four pupils in each of the eight schools were used for the study, totaling 325 pupils. The selection of primary four pupils arose from the fact that they were free from any immediate external examination, therefore, the schools administrators readily made the pupils available for the study. The treatment lasted ten weeks. The participants were randomised into DBIS (91), PSBIS (96), PBIS (69) and control (69) groups. Instructional guide for DBIS, PSBIS, PBIS and control, Pupils‘ Awareness to Child Rights (r=0.76) and Pupils' Attitude to Child Rights (r=0.85) questionnaires were used for data collection. Data were analysed using descriptive statistic and Analysis of Covariance at 0.05 level of significance. Treatment had significant main effect on pupils‘ attitude to child rights (F(3,308)=3.16, η2=0.03) but not on awareness. Participants in PSBIS had the highest attitude mean score (33.53), followed by those in PBIS (32.87), DBIS (32.04) and control groups (30.76). School location and parents‘ educational background had no significant main effect on pupils‘ awareness and attitude to child rights. The 2-way interaction effect of treatments and school location was not significant on pupils‘ awareness but was significant on pupils‘ attitude to child rights (F(3,308)=7.60,η2=0.07). Participants in urban schools had mean score of (31.99) while rural had mean score of (32.61). Poetry/song and prose strategies enhanced pupils‘ attitude significantly better than drama and conventional strategies. Poetry/song, drama and prose-based instructional strategies enhanced pupils‘ attitude to child rights. Hence, stakeholders in child rights protection and child educators could adopt these strategies to positively change pupils‘ attitude to child rights.